Employees‟ Perception on their Superiors‟ Leadership style and its relationship with Fostering Innovation Culture in Manufacturing Industry in Penang, Malaysia. - Yuan Lin, Richie Chan (2012)
Kajian kuantitatif adalah untuk meramalkan hubungan antara gaya kepimpinan pemimpin memupuk budaya inovasi.